1998
DOI: 10.1128/jvi.72.4.2975-2982.1998
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Type 5 E4 Open Reading Frame 4 Protein Induces Apoptosis in Transformed Cells

Abstract: Adenovirus type 5 E4 open reading frame 4 (E4orf4) protein has been previously shown to counteract transactivation of the junBand c-fos genes by cyclic AMP plus E1A protein and to interact with protein phosphatase 2A (PP2A). Here, we show that the wild-type E4orf4 protein induces apoptosis in the E1A-expressing 293 cells, in NIH 3T3 cells transformed with v-Ras, and in the lung carcinoma cell line H1299. The induction of apoptosis is not accompanied by enhanced levels of p53 in 293 cells and occurs in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(47 citation statements)
references
References 55 publications
3
44
0
Order By: Relevance
“…Adenovirus E4orf4 protein is a multifunctional protein. Our work, as well as work from other laboratories, has shown that the E4orf4 protein down regulates expression of genes that have been activated by E1A and cAMP (MuÈ ller et al, 1992;Kleinberger and Shenk, 1993), induces hypophosphorylation of various viral and cellular proteins (MuÈ ller et al, 1992;Kanopka et al, 1998), regulates alternative splicing of adenovirus mRNAs (Kanopka et al, 1998), and induces p53-independent apoptosis in transformed cells Marcellus et al, 1998;Shtrichman and Kleinberger, 1998). We have previously shown that E4orf4 interacts with the PP2A holoenzyme through a direct association with the a isoform of the B subunit (Ba) (Kleinberger and Shenk, 1993).…”
Section: Introductionsupporting
confidence: 53%
“…Adenovirus E4orf4 protein is a multifunctional protein. Our work, as well as work from other laboratories, has shown that the E4orf4 protein down regulates expression of genes that have been activated by E1A and cAMP (MuÈ ller et al, 1992;Kleinberger and Shenk, 1993), induces hypophosphorylation of various viral and cellular proteins (MuÈ ller et al, 1992;Kanopka et al, 1998), regulates alternative splicing of adenovirus mRNAs (Kanopka et al, 1998), and induces p53-independent apoptosis in transformed cells Marcellus et al, 1998;Shtrichman and Kleinberger, 1998). We have previously shown that E4orf4 interacts with the PP2A holoenzyme through a direct association with the a isoform of the B subunit (Ba) (Kleinberger and Shenk, 1993).…”
Section: Introductionsupporting
confidence: 53%
“…E4orf6 MUTANT ANALYSIS sively antagonizes cellular transformation through a unique p53-independent mechanism (25,32,53,54). Recently, we and others have shown that the Ad5 E4orf6 and E4orf3 gene products exhibit E1B-like transforming prop-erties in that they can individually cooperate with Ad5 E1A to initiate focus formation in primary baby rat kidney (BRK) cells.…”
Section: Vol 74 2000mentioning
confidence: 99%
“…Recently, we and others have shown that expression of the Ad E4orf4 protein in several mammalian cell lines induces a p53-independent apoptotic pathway (Shtrichman and Kleinberger 1998;Lavoie et al 1998; Marcellus et al 1998). E4orf4 appears to kill transformed cells more selectively, as expression of oncogene in primary cell cultures was reported to sensitize these cells to E4orf4-induced apoptosis (Shtrichman et al 1999).…”
Section: Introductionmentioning
confidence: 99%